2013
DOI: 10.1261/rna.040931.113
|View full text |Cite
|
Sign up to set email alerts
|

SHAPE analysis of the 5′ end of the Mason-Pfizer monkey virus (MPMV) genomic RNA reveals structural elements required for genome dimerization

Abstract: Earlier genetic and structural prediction analyses revealed that the packaging determinants of Mason Pfizer monkey virus (MPMV) include two discontinuous core regions at the 5 ′ end of its genomic RNA. RNA secondary structure predictions suggested that these packaging determinants fold into several stem-loops (SLs). To experimentally validate this structural model, we employed selective 2 ′ hydroxyl acylation analyzed by primer extension (SHAPE), which examines the flexibility of the RNA backbone at each nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
79
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(84 citation statements)
references
References 53 publications
(86 reference statements)
4
79
1
Order By: Relevance
“…The specificity for gRNA during packaging, thus, has been ascribed to high-affinity interactions between the NC domain of Gag and the packaging signal [513]. We have made a similar observation in the case of MPMV, where genetic and structure-prediction analyses have suggested that either ssPurines (Region A) or its partially repeated but base-paired sequence (Region B) plays a crucial role in gRNA packaging, possibly by functioning as a NC binding site [32,33]. …”
Section: Discussionmentioning
confidence: 71%
See 4 more Smart Citations
“…The specificity for gRNA during packaging, thus, has been ascribed to high-affinity interactions between the NC domain of Gag and the packaging signal [513]. We have made a similar observation in the case of MPMV, where genetic and structure-prediction analyses have suggested that either ssPurines (Region A) or its partially repeated but base-paired sequence (Region B) plays a crucial role in gRNA packaging, possibly by functioning as a NC binding site [32,33]. …”
Section: Discussionmentioning
confidence: 71%
“…Several riboswitch models have been proposed for HIV-1 [5053], and in the case of FIV, the existence of dual structures has been validated by SHAPE and RNA dimerization assays [54]. Flexibility in retroviral gRNA is created via long-range interactions that have now been observed in several retroviruses, from HIV-1, FIV, MLV, to MPMV and MMTV [6,25,26,33,5559]. The DIS in one conformation is occluded by base pairing and not available for dimerization, thus earmarking this RNA for translation, while the DIS in the other conformation is available as an apical loop on a stem loop, thus allowing dimerization and packaging of the dimeric RNA [54].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations